2021
DOI: 10.1039/d1nr02307a
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for preparing high-efficiency and economical catalytic electrodes toward overall water splitting

Abstract: The technology of electrolyzing water to prepare high-purity hydrogen is an important field in today's energy development. However, how to prepare efficient, stable, and inexpensive hydrogen production technology from electrolyzed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 269 publications
0
39
0
Order By: Relevance
“…It also enhances several properties such as mass/charge transfer resistance, and ensures maximum utilization of active material by improving the surface area and enhancing exposure to the active sites, structural stability, and mechanical strength. [73,74] The advantages of different electrode supports have been discussed in detail in a review article published by Yao et al [75] 2.1.6. 3D Ni-Foam 3D Ni-foam is a widely used conducting substrate for energy storage and conversion application, including electrochemical water splitting.…”
Section: Free-standing Growth Of Zif-67mentioning
confidence: 99%
See 1 more Smart Citation
“…It also enhances several properties such as mass/charge transfer resistance, and ensures maximum utilization of active material by improving the surface area and enhancing exposure to the active sites, structural stability, and mechanical strength. [73,74] The advantages of different electrode supports have been discussed in detail in a review article published by Yao et al [75] 2.1.6. 3D Ni-Foam 3D Ni-foam is a widely used conducting substrate for energy storage and conversion application, including electrochemical water splitting.…”
Section: Free-standing Growth Of Zif-67mentioning
confidence: 99%
“…[ 73,74 ] The advantages of different electrode supports have been discussed in detail in a review article published by Yao et al. [ 75 ]…”
Section: Synthesis Strategies For Zif‐67 Mofmentioning
confidence: 99%
“…Therefore, when the adsorption and desorption rates of reaction intermediates reach a dynamic equilibrium, the catalyst exhibits satisfying activity. [42][43][44] As mentioned above, the oxygen-rich surface of POMs can be regarded as a proton acceptor, attracting the reaction intermediates. POMOCs have precise and controllable active sites, which can facilitate electron and proton transfer during the HER.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%
“…26 The commercial exploitation of 3D flexible substrates not only provides a larger specific surface area, more reactive sites, and faster gas release rates, but also reduces the preparation cost and they are applicable in hydrogen production under harsh conditions. Our previous work designed a Ni-P-B@paper standing-free electrode by electroless plating, which worked stably in an alkaline electrolyte at 1000 mA cm −2 for 240 h. 27 Other research groups also reported a series of flexible electrodes such as wearable carbon cloth 28,29 and hydrophilic sponges, 27,30 indicating that flexible electrodes have remarkable mechanical robustness, low overpotentials and long-term durability after rational surface modification and structural engineering. Yet, it was predicted that by 2030 53 million tons of "white plastic" waste may be dumped directly into contaminated oceans and other aquatic environments every year.…”
Section: Introductionmentioning
confidence: 99%